Systematic design and evaluation of aptamers for VEGF and PlGF biomarkers of Preeclampsia - Mallawarachchi, Samavath; Cebecioğlu, Rümeysa Emine; Althumayri, Majed; Beker, Levent; Fernando, Sandun; Koydemir, Hatice Ceylan (Springer Nature, 2024)
Preeclampsia is a potentially life-threatening condition for both mother and baby, characterized by hypertension and potential organ damage. Early diagnosis is crucial to mitigate its adverse health effects. Traditional diagnostic methods, which focus on late-manifesting symptoms like hypertension and proteinuria, underscore the need for molecular diagnostic approaches for timely detection. This study successfully designs and evaluates novel aptamers with high specificity and affinity for Vascular Endothelial Growth Factor (VEGF) and Placental Growth Factor (PlGF), biomarkers closely associated with preeclampsia. Using molecular docking, molecular dynamics simulations, and BioLayer Interferometry (BLI), we identified aptamers that demonstrated strong binding affinities, comparable or superior to traditional antibodies. Our findings suggest that these aptamers have the potential to be integrated into cost-effective, point-of-care diagnostic tools, significantly improving early detection and intervention strategies for preeclampsia. The robust performance of these aptamers marks a pivotal step toward the development of more reliable and accessible diagnostic solutions, with implications for better maternal and fetal health outcomes.
Keywords: Preeclampsia; VEGF; PlGF; Aptamer; Diagnostics; Aptasensor; Bio-layer interferometry